Effect of silane coupling treatments on mechanical properties of epoxy based high-strength carbon fiber regular (2 x 2) braided fabric composites - SANCAK, ERHAN; ERYILMAZ, OĞUZ (WILEY, 2021)
Braiding technique is one of the most cost-effective and versatile methods to manufacture braided preforms for producing textile reinforced composites. Carbon fiber is one of the most common reinforcing fibers having high strength and modulus used in high-performance composites. In this study, epoxy resin was modified with 3-aminopropyltriethoxysilane (APTES) and 3-aminopropylmethyldimethoxysilane (APMDMS) in order to enhance interfacial adhesion between matrix and carbon fiber. Composites were produced by vacuum-assisted resin infusion method using braided fabrics which were manufactured from a high-strength standard modulus type of carbon fiber (T700S) by using a radial braiding machine. Epoxy resin was treated with silane at different concentrations from 0.0% to 1.0%. According to the mechanical results, the ideal (optimum) concentration of APTES and APMDMS for the matrix modification has been around 0.5 wt% of the epoxy system. Also, the mechanical properties of APTES-treated epoxy composites are slightly higher than those of APMDMS-treated epoxy composites at the same concentration. When it is compared to silane untreated composite, 0.5 wt% of APTES/APMDMS silane treated epoxy/carbon braided composites have led to an increase of 7.71/6.16% and 7.65/6.05% in tensile and flexural strength while the corresponding increase has resulted in 17.48/13.51% and 16.63/13.33% in terms of tensile and flexural modulus, respectively. Impact testing results indicate that 0.5 wt% of APTES and APMDMS composites are improved 6.87% and 4.31% compared to untreated composites, respectively.
Keywords: braiding; carbon fiber; composite; mechanical properties; silane coupling agents; GLASS-FIBER; TENSILE PROPERTIES; IMPACT PROPERTIES; BASALT; SURFACE; AGENTS